Stagnasi Pemilu Orde Lama, Orde Baru, dan Orde Reformasi dalam Ketatanegaraan Indonesia Menuju Pemilu Ideal - Julman Hente; Siti Fatimah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2026)
This study examines the dynamics and stagnation of elections in Indonesia across three major political eras, the Old Order, the New Order, and the Reform Era, from a constitutional law perspective in pursuit of an ideal electoral system. Employing a normative legal research method with statutory, historical, and philosophical approaches, this study identifies that each era left distinct yet interconnected patterns of electoral stagnation. During the Old Order, the 1955 General Election was recognized as the most democratic, with a voter turnout of 91.54%; however, a multi-party system lacking adequate consolidation mechanisms led to severe political fragmentation, ultimately culminating in the imposition of Guided Democracy. During the New Order, six consecutive elections were held from 1971 to 1997. Still, they were democratically hollow, as Golkar consistently won through systematic manipulation that reduced elections to mere instruments of power legitimation. The Reform Era introduced political liberalization and strengthened independent electoral institutions. Yet, new forms of stagnation emerged: oligarchic dominance, rampant money politics, and alleged electoral fraud that continued to undermine electoral integrity through the 2024 General Election. This study concludes that achieving an ideal election requires systemic reformulation encompassing the constitutional strengthening of electoral institution independence, equitable redesign of the electoral system, transparent campaign finance oversight, bureaucratic neutrality, and enhanced civic and political education, so that elections not only fulfill the procedural principles of direct, general, free, secret, honest, and fair voting, but also effectively produce accountable representatives who genuinely reflect the substantive sovereignty of the people.